Renal Replacement in the Critically ill with Acute Kidney Injury: When and How to Initiate Therapy - Natasha, Susmita Hossain; Faruq, Mohammad Omar (Bangladesh Critical Care Journal, 2024)
Although Acute Kidney Injury (AKI) is a common complication in the critically ill, there is still no specific therapy. Similarly the diagnosis of AKI, while regulated by specific criteria, is not free from pitfalls. Newer biomarkers are also being added in the diagnostic panel that helps in identifying the stage, severity and underlying cause of this condition. When preventive and supportive management fails, Renal Replacement Therapy (RRT) becomes necessary. RRT is one of the most invasive management procedures and it is associated with many complications. Hence the time of onset and the modality of choice are two of the most puzzling aspects of this procedure. Over the last decade and a half, a lot of RCTs, observational studies and meta analyses have been carried to find the exact answer to these questions. While all the answers are not yet simplified, we have specific guiding parameters now as to the choice of modality and onset of dialysis for AKI. There is still need for further research for more specific answers to these age old questions. Bangladesh Crit Care J September 2024; 12 (2): 153-159